Perancangan Aplikasi Tajwid Asyik (Tasik) Sebagai Media Pembelajaran Tajwid - Rasyid, Muhammad Fadhil Al; Arifin, Aridhanyati (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Tajweed science is a science that is used to be able to read the Al-Quran properly and correctly. Tajweed learning is generally in the form of lectures and exercises under the guidance of the teacher using manuals. It's just that learning becomes monotonous and inflexible. Whereas learning media plays an important role in the learning process. Along with the development of smartphone technology, the use of mobile-based learning media (mobile learning) can be a supporting medium for learning that is more interactive and flexible in terms of time and place. Mobile-based learning is proven to increase students' understanding. This paper will describe the design of the TASIK application by applying the 3 stages of the ADDIE model, namely focusing on Analyze, Design and Develop. The software development method used is waterfall. The focus of research is on the front-end side of the application. The research subjects were members of the TPA Nurul Islam Mosque, Balikpapan, East Kalimantan, with a minimum age of 10 years. Based on blackbox testing, it is known that all functions in the TASIK application are running well. The SUS test results show that users can accept applications with a score of 81.67.